Remixed a study on the effect of the surge in foreign music concerts in the Philippines on the Original Pilipino Music coverage of two music magazines Pulp and Myx from 2010 to 2013 - Regondola, Antonio Lorenzo F. (2014)
"This thesis examines the coverage of Original Pilipino Music (OPM) in PULP and Myx Magazine as a response to the influx of foreign artists visiting the country to perform concerts, a trend which the researcher estimated to have begun at around 2010. As the two longest-running music magazines in the country, PULP and Myx were the most appropriate materials to research about this topic. The Agenda Setting theory and the Culture Industry concept were the theoretical frameworks upon which the research operated. The study employed both quantitative and qualitative methods: (1) content analysis to examine the articles found in the magazines, and (2) interviews with editors of the magazines to clarify the data previously gathered. It was found that, while there are more OPM-related stories in PULP, there has been a decrease in terms of the space occupied by PULP's articles, Myx Magazine, on the other hand, had more foreign-related stories, but OPM-related stories occupied more space. Overall, PULP's OPM coverage has clearly decreased as a result of foreign artist upsurge, while Myx Magazine's OPM coverage remained constant despite this influx."